2000
DOI: 10.1164/ajrccm.162.6.9908097
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Growth Factor Attenuates Collagen Accumulation in a Murine Model of Pulmonary Fibrosis

Abstract: We investigated the in vivo effects of recombinant human hepatocyte growth factor (HGF) on epithelial cell proliferation in normal mouse lung and on the repair process that follows bleomycin-induced lung injury. Intratracheal administration of 100 micrograms of rhHGF to C57BL/6 mice led to proliferation of bronchial and alveolar epithelial cells as indicated by an increased number of cells staining for proliferating cell nuclear antigen (PCNA). The effect of HGF on the lung repair process was examined by admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
126
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(130 citation statements)
references
References 31 publications
4
126
0
Order By: Relevance
“…Li, Azuma, Takahashi et al, 2002) etc. ), Cytokines (Interferon-β (Azuma, Li et al, 2005), Interferon-γ (Gurujeyalakshmi & Giri, 1995;Hyde, Henderson, Giri, Tyler, & Stovall, 1988;Okada, Sugie, & Aisaka, 1993), Interleukin (IL)-1beta (M. Yasui et al, 1991), IL-10 (Arai et al, 2000), IL-18 (Nakatani-Okuda et al, 2005), Keratinocyte growth factor (Deterding et al, 1997;Sugahara, Iyama, Kuroda, & Sano, 1998;Yi et al, 1996), Hepatocyte growth factor (Dohi, Hasegawa, Yamamoto, & Marshall, 2000;Mizuno, Matsumoto, Li, & Nakamura, 2005;Umeda et al, 2004;Yaekashiwa et al, 1997), Chemokine ligand (CXCL)-10 (Tager et al, 2004),CXCL11 (Burdick et al, 2005), CD (cluster of differentiation)-36 (Yehualaeshet et al, 2000) etc. ), Cytokine antibodies (Transforming growth factor-β (Giri, Hyde, & Hollinger, 1993), Tumor necrosis factor-α (Fichtner-Feigl, Strober, Kawakami, Puri, & Kitani, 2006;Fujita et al, 2003;Piguet & Vesin, 1994), Connective tissue growth factor (Matsuoka et al, 2002), IL-12 , IL-13 (Fichtner-Feigl, Strober, Kawakami, Puri, & Kitani, 2006), Platelet derived growth factor (Aono et al, 2005;Chaudhary, Schnapp, & Park, 2006;Daniels et al, 2004;Yoshida et al, 1999), Vascular endothelial growth factor (Hamada et al, 2005), CCR-1 (Tokuda et al, 2000), CCR-3 (Huaux et al, 2005), CCL-11 (Huaux et al, 2005), CD-11 (Piguet, Rosen, Vesin, & Grau, 1993), MCP-1 etc.…”
Section: Drug Intervention Studies In the Bleomycin Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Li, Azuma, Takahashi et al, 2002) etc. ), Cytokines (Interferon-β (Azuma, Li et al, 2005), Interferon-γ (Gurujeyalakshmi & Giri, 1995;Hyde, Henderson, Giri, Tyler, & Stovall, 1988;Okada, Sugie, & Aisaka, 1993), Interleukin (IL)-1beta (M. Yasui et al, 1991), IL-10 (Arai et al, 2000), IL-18 (Nakatani-Okuda et al, 2005), Keratinocyte growth factor (Deterding et al, 1997;Sugahara, Iyama, Kuroda, & Sano, 1998;Yi et al, 1996), Hepatocyte growth factor (Dohi, Hasegawa, Yamamoto, & Marshall, 2000;Mizuno, Matsumoto, Li, & Nakamura, 2005;Umeda et al, 2004;Yaekashiwa et al, 1997), Chemokine ligand (CXCL)-10 (Tager et al, 2004),CXCL11 (Burdick et al, 2005), CD (cluster of differentiation)-36 (Yehualaeshet et al, 2000) etc. ), Cytokine antibodies (Transforming growth factor-β (Giri, Hyde, & Hollinger, 1993), Tumor necrosis factor-α (Fichtner-Feigl, Strober, Kawakami, Puri, & Kitani, 2006;Fujita et al, 2003;Piguet & Vesin, 1994), Connective tissue growth factor (Matsuoka et al, 2002), IL-12 , IL-13 (Fichtner-Feigl, Strober, Kawakami, Puri, & Kitani, 2006), Platelet derived growth factor (Aono et al, 2005;Chaudhary, Schnapp, & Park, 2006;Daniels et al, 2004;Yoshida et al, 1999), Vascular endothelial growth factor (Hamada et al, 2005), CCR-1 (Tokuda et al, 2000), CCR-3 (Huaux et al, 2005), CCL-11 (Huaux et al, 2005), CD-11 (Piguet, Rosen, Vesin, & Grau, 1993), MCP-1 etc.…”
Section: Drug Intervention Studies In the Bleomycin Modelmentioning
confidence: 99%
“…HGF acts on epithelial cells as a mitogen, stimulating migration and morphogenesis (Dohi, Hasegawa, Yamamoto, & Marshall, 2000;Yaekashiwa et al, 1997). It is described as potent inducer of matrix metalloproteinases (MMPs), which degrade extracellular matrix and are overexpressed during progression of myofibroblast apoptosis (Mizuno, Matsumoto, Li, & Nakamura, 2005).…”
Section: Hepatocyte Growth Factor (Hgf)mentioning
confidence: 99%
See 1 more Smart Citation
“…These increases are significant because inhibition of HGF activity in the lung in animal models worsens lung fibrosis (14). Conversely, interventions designed to increase HGF reduce scarring (22)(23)(24). For HGF to have its effect on target cells, it must undergo several extracellular processing events (15,16).…”
mentioning
confidence: 99%
“…Numerous studies have shown HGF to be an endogenous antifibrotic factor in the lungs, ameliorating fibrotic lesions and preserving lung function in experimental animal models of pulmonary fibrosis (22)(23)(24)(25). HGF exerts its antifibrotic effects on pulmonary function by reducing the production of type I collagen and CTGF, and increasing the production of matrix metalloproteinase 1 in lung fibroblasts (12,26).…”
Section: Discussionmentioning
confidence: 99%